Power, tourism, and ecology: a critical inquiry into aconcagua’s power structures and conceptions of nature - Henry Mooney (Cogent Social Sciences)
This paper offers a multifaceted examination of the core-periphery dynamics inherent in the utilization and conceptualization of nature within Aconcagua Provincial Park (APP). Drawing on ethnographic data and textual analysis, it scrutinizes the interplay between historical legacies, economic imperatives, and ecological outcomes shaping mountaineering tourism within the park. The study reveals a complex web of power relations, economic exploitation, and ecological degradation perpetuating a commodified view of nature, consistent with other political ecological literature in montane environments. By analyzing the operational dynamics of APP and mountaineering tourism in and beyond southern Andean contexts, this work unveils how core state interests influence or dictate land use, resource management, and access to the park. Furthermore, it points toward the inadequacy of existing management frameworks in addressing systemic issues like ecologically deleterious behaviors. This research contributes to political ecology scholarship by illuminating co-constructed narratives on nature, politics, and societal structures in high mountain areas which can overlook the profound effects of power dynamics and economic interests on local ecology in managed park systems in periphery states.